Factors Associated with Bullying Behavior among Adolescents in a Junior High School - Lia Dwi Jayanti; Rahma Wulan Safitri; Tri Wiji Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Bullying is a form of aggressive behavior commonly experienced by adolescents and has significant impacts on both physical and mental health. Schools, as primary social environments for teenagers, often become settings where bullying occurs. Several factors contribute to this behavior, particularly peer influence, family roles, and social media use. This study aimed to analyze factors related to bullying behavior among adolescents in a junior high school, including respondent characteristics, peer influence, family roles, and social media usage, as well as their relationships with bullying behavior. This research used a quantitative approach with a cross-sectional design involving 71 eighth-grade students as respondents. Data were collected using structured questionnaires and analyzed with the Chi-Square test. The results showed significant relationships between peer factors (p=0.003), family roles (p<0.001), and social media use (p=0.001) with bullying behavior. A large proportion of respondents reported high social media usage (45.1%) and low family involvement (45.1%), while more than half (53.5%) were categorized as being at risk of engaging in bullying behavior. These findings indicate that adolescents are strongly influenced by their social environment, both offline and online. Negative peer interactions and limited family supervision can increase the likelihood of bullying behavior. In conclusion, peer factors, family roles, and social media use are significantly associated with bullying among adolescents. Therefore, collaboration between families, schools, and communities is essential through psychosocial assessments, increased family involvement, and character education programs to prevent and reduce bullying behavior.